Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia - Purwanda, Sunardi; Rezky Wulandari, Andi Sri (Al-'Adl, 2023)
The purpose of the study is to analyze the position of socio-legal studies in legal studies, to analyze their intersection with similar studies, and to analyze their methodical implications for the development of law in Indonesia. By merging doctrinal legal approaches and empirical legal approaches, socio-legal studies appear to offer a large field for legal scholars using a variety of methods. In the study of legal phenomena that are not isolated by social, political, economic, or cultural circumstances, socio-legal studies place concepts and theories based on an interdisciplinary approach that combines disciplines. The sociology of law, which primarily draws its intellectual inspiration from mainstream sociology and views law as a vehicle for social governance, a profession, and a discipline, is distinct from socio-legal studies. Legal discourse, which is a common occurrence in everyday life, is a major subject of legal sociology. Additionally, Socio-Legal Studies differ from Sociological Jurisprudence, which emphasizes realism viewpoints in the field of law.